Non-sterile Submerged Fermentation of Fibrinolytic Enzyme by Marine Bacillus subtilis Harboring Antibacterial Activity With Starvation Strategy - Pan, Shihan; Chen, Guiguang; Wu, Rui; Cao, Xiaoyan; Liang, Zhiqun (Frontiers in Microbiology, 2019)
Microbial fibrinolytic enzyme is a promising candidate for thrombolytic therapy. Non-sterile production of fibrinolytic enzyme by marine Bacillus subtilis D21-8 under submerged fermentation was realized at a mild temperature of 34°C, using a unique combination of starvation strategy and self-production of antibacterial agents. A medium composed of 18.5 g/L glucose, 6.3 g/L yeast extract, 7.9 g/L tryptone, and 5 g/L NaCl was achieved by conventional and statistical methods. Results showed efficient synthesis of fibrinolytic enzyme and antibacterial compounds required the presence of both yeast extract and tryptone in the medium. At shake-flask level, the non-sterile optimized medium resulted in higher productivity of fibrinolytic enzyme than the sterile one, with an enhanced yield of 3,129 U/mL and a production cost reduced by 24%. This is the first report dealing with non-sterile submerged fermentation of fibrinolytic enzyme, which may facilitate the development of feasible techniques for non-sterile production of raw materials for the preparation of potential drugs with low operation cost.